Remote Microphone System Use at Home: Impact on Child-Directed Speech - Benítez-Barrera, Carlos R. (J Speech Lang Hear Res, 2019)
PURPOSE: The impact of home use of a remote microphone system (RMS) on the caregiver production of, and child access to, child-directed speech (CDS) in families with a young child with hearing loss was investigated. METHOD: We drew upon extant data that were collected via Language ENvironment Analysis (LENA) recorders used with 9 families during 2 consecutive weekends (RMS weekend and no-RMS weekend). Audio recordings of primary caregivers and their children with hearing loss obtained while wearing and not wearing an RMS were manually coded to estimate the amount of CDS produced. The proportion of CDS that was likely accessible to children with hearing loss under both conditions was determined. RESULTS: Caregivers produced the same amount of CDS when using and when not using the RMS. However, it was concluded that children with hearing loss, on average, could potentially access 12% more CDS if caregivers used an RMS because of their distance from their children when talking to them. CONCLUSION: Given our understanding of typical child language development, findings from this investigation suggest that children with hearing loss could receive auditory, speech, and language benefits from the use of an RMS in the home environment.